Breaking Down the State: Protestors Engaged - Duyvendak, Jan Willem; Jasper, James M. (Protest and Social Movements, 2015)
In this important book, Jan Willem Duyvendak and James M. Jasper bring together an internationally acclaimed group of contributors to demonstrate the complexities of the social and political spheres in various areas of public policy. By breaking down the state into the players who really make decisions and pursue coherent strategies, these essays provide new perspectives on the interactions between political protestors and the many parts of the state-from courts, political parties, and legislators to police, armies, and intelligence services. By analyzing politics as the interplay of various players within structured arenas, Breaking Down the State provides an innovative look at law and order versus opposition movements in countries across the globe.